Promuovere lo sviluppo della competenza geometrica: una ricerca nella scuola dell'infanzia - Maeca Garzia; Antonietta Esposito (LED Edizioni Universitarie, 2024)
PROMOTING THE DEVELOPMENT OF GEOMETRIC COMPETENCE: A RESEARCH IN KINDERGARTENS Abstract Conducting a research in kindergartens, whose intended impact on the development of children's geometric competence is to facilitate their learning in later educational stages, involved the collaboration between a pedagogical researcher and a disciplinarian teacher. This collaboration between different areas of expertise represents a key strength of the research presented in this article, which aims at contributing to the reorganisation of curriculum in kindergartens. Through an empirical approach, the research wants to demonstrate the impact that a laboratory teaching path, involving the transition from solid to plane geometry and CAD modelling with 3D printing, can have on classification, representation and sectioning skills of geometric shapes by children at the age of 5.